Development and model test of dynamic loading system in mine goaf site for high-speed railway subgrade - Lianwei REN; Liang LI; Ziqiang WANG; Youfeng ZOU; Zhilin DUN; Shuren WANG (Meitan xuebao)
With the rapid advancement of the high-speed railway network, it is inevitable that some key lines will cross the mininggoaf site. This poses higher requirements for the construction, safe operation, and maintenance of high-speed railways. To address these scientific issues, the development of related test systems becomes an important approach for a comprehensive study. However, there is a lack of relevant test systems both domestically and internationally. To fill this gap, a dynamic loading model test system for high-speed railway subgrade in mininggoaf sites has been developed. This system involves the creation of a two-dimensional high-speed railway subgrade model with a geometric similarity ratio of 1∶100. By using a three-stage Fourier series fitting, the 40 Hz high-speed railway M-wave corresponding to a speed of 360 km/h is obtained when the similarity constant is 100. Additionally, the system allows for the realization of the M-wave output of high-speed load within a 10% error, thereby verifying the feasibility of dynamic loading tests for the high-speed railway subgrade models in mining goaf areas. The system also enables the performance of 1 million uninterrupted M-wave cyclic loadings for high-speed railways. This study examines the causes of the triangular separation space under the main key stratum and discusses the transmission path of dynamic load in the overburden rock of the goaf at different loading stages. It analyzes the interaction between the caving fault zone and the bending deformation zone under dynamic load, and reveals the activation mechanism of the foundation in the goafunder a high-speed rail load. The research findings indicate that the activation space of the overburden rock gradually decreases from the moving boundary to the center of the collapsed overburden rock, and the horizontal separation of the overburden rock gradually increases from the roof to the key stratum, thus explaining the cause of the triangular separation space under the main key stratum. The triangle abscission layer space acts as an isolation barrier, requiring the transfer of dynamic load downward to the caving fault zone through the tensile zone of the moving boundary of the overlying rock during the initial stage of loading. The masonry beam structure, which first affects the moving boundary, becomes unstable and activated. With the application of dynamic load, the separation space under the main key stratum gradually closes, causing the dynamic load transfer path to shift towards the center of the goaf. The residual activated settlement continues to transfer upward, resulting in an overall settlement that tends to be more gentle. The change in load transfer path leads to the activation of the caving fracture zone, which initially occurs rapidly and then slows down, extending from the stop line to the middle of the goaf. The activation of the collapse fault zone further impacts the stress distribution in the overlying rock above the main key layer and causes an uneven settlement on the model surface. This results in the formation of three types of cracks (transverse, vertical, and inclined) in the bending deformation zone, which are distributed along both sides of subgrade.